The Impact Of Antecedents And Outcome Of Electronic Word-Of-Mouth On Online Airline Tickets Purchase Intention By Malaysian - Lunyai, Janifer (2020)
The primary objective of this study has been to identify the antecedents of electronic Word-of-Mouth (eWOM) in the context of online airline ticket purchase by Malaysian consumers. In addition, this study also seeks to examine the relationship between eWOM and purchase intention and to propose a research model for the antecedents of eWOM and its impact on purchase intention. S-O-R Model and ELM Model were adopted as the referent theory for this study. The research model was examined by employing survey questionnaire method obtained from 530 Malaysian consumers through mall-intercept method.